A risk score to predict postdischarge bleeding among acute coronary syndrome patients undergoing percutaneous coronary intervention: BRIC‐ACS study. Issue 7 (21st May 2019) - Chen, Yundai; Yin, Tong; Xi, Shaozhi; Zhang, Shuyang; Yan, Hongbing; Tang, Yida; Qian, Juying; Chen, Jiyan; Su, Xi; Du, Zhimin; Wang, Lefeng; Qin, Qin; et al.
Abstract: Background: Dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) prevents ischemic events while increasing bleeding risk. Real‐world‐based metrics to accurately predict postdischarge bleeding (PDB) occurrence and its potential impact on postdischarge major cardiovascular event (MACE) remain undefined. This study sought to evaluate the impact of PDB on MACE occurrence, and to develop a score to predict PDB risk among Chinese acute coronary syndrome (ACS) patients after PCI. Methods and Results: From May 2014 to January 2016, 2496 ACS patients who underwent PCI were recruited consecutively from 29 nationally representative Chinese tertiary hospitals. Among 2, 381 patients (95.4%, 2, 381/2, 496) who completed 1‐year follow‐up, the cumulative incidence of PDB (bleeding academic research consortium type [BARC] ≥2) and postdischarge MACE (a composite of all‐cause death, nonfatal myocardial infarction, ischemic stroke, or urgent revascularization) was 4.9% ( n = 117) and 3.3% ( n = 79), respectively. The association between PDB and MACE during 1‐year follow‐up, as well as the impact of DAPT with ticagrelor or clopidogrel on PDB were evaluated. PDB was associated with higher risk of postdischarge MACE (7.7 vs. 3.1%; adjusted hazard ratio: 2.59 [95% confidence interval: 1.17–5.74]; p = .02). For ticagrelor versus clopidogrel, PDB risk was higher (8.0 vs. 4.4%; 2.05 [1.17–3.60]; p = .01), while MACE risk was similar (2.0 vs. 3.4%; 0.70 [0.25–1.93]; p = .49). Based on identified PDB predictors, the constructed bleeding risk in real world Chinese acute coronary syndrome patients (BRIC‐ACS) score for PDB was established. C‐statistic for the score for PDB was 0.67 (95% CI: 0.62–0.73) in the overall cohort, and >0.70 in subgroups with non‐ST‐ and ST‐segment elevation myocardial infarction, diabetes and receiving more than two drug eluting stents. Conclusions: In Chinese ACS patients, PDB with BARC ≥2 was associated with higher risk for MACE after PCI. The constructed BRIC‐ACS risk score provides a useful tool for PDB discrimination, particularly among high ischemic and bleeding risk patients.